Christian Education as Prophetic Action: Integrating Social Theology to Promote Justice and Societal Transformation - Zalukhu, Amirrudin (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2025)
Christian education serves as a prophetic action of the Church, reflecting its commitment to promoting justice within the framework of social theology. In an era marked by widening inequalities, systemic oppression, and moral ambiguity, the Church faces an urgent need to respond with transformative educational practices that go beyond doctrinal instruction. This study explores the role of Christian education in addressing social injustices and fostering societal transformation through a qualitative literature review approach. The research emerges from the growing concern that traditional ecclesial education often fails to engage critically with social realities. Drawing from Paulo Freire’s critical pedagogy, this study underscores the liberating potential of education as a practice of freedom—empowering learners to become conscious agents of change. Freire argues that true education must foster critical reflection and action (praxis) to challenge structures of domination. Similarly, Gustavo Gutiérrez’s theology of liberation informs the study by framing justice as a core element of Christian mission. This research examines the theological foundations of justice within Christian social thought and how Christian education embodies the Church’s prophetic mission by integrating justice-oriented values into its curriculum. The findings highlight the synergy between social theology and education, while identifying challenges such as cultural resistance, theological rigidity, and institutional inertia. The study concludes by advocating for a justice-focused educational model that equips believers to embody the Church’s prophetic voice in society.AbstrakPendidikan Kristen berfungsi sebagai tindakan profetik Gereja, yang mencerminkan komitmennya untuk mempromosikan keadilan dalam kerangka teologi sosial. Di tengah meningkatnya ketimpangan, penindasan sistemik, dan krisis moral, Gereja menghadapi kebutuhan mendesak untuk merespons dengan praktik pendidikan yang transformatif dan melampaui pengajaran doktrinal semata. Studi ini mengeksplorasi peran pendidikan Kristen dalam menanggapi ketidakadilan sosial dan mendorong transformasi masyarakat melalui pendekatan tinjauan pustaka kualitatif. Penelitian ini muncul dari keprihatinan bahwa pendidikan gerejawi tradisional sering kali gagal terlibat secara kritis dengan realitas sosial. Mengacu pada pedagogi kritis Paulo Freire, studi ini menekankan potensi pendidikan sebagai praktik pembebasan—memberdayakan peserta didik untuk menjadi agen perubahan yang sadar. Freire berpendapat bahwa pendidikan sejati harus mendorong refleksi kritis dan tindakan(praxis) untuk menantang struktur penindasan. Sejalan dengan itu, teologi pembebasan Gustavo Gutiérrez memberikan dasar bahwa keadilan merupakan elemen utama dari misi Kristen. Penelitian ini menelaah landasan teologis keadilan dalam pemikiran sosial Kristen serta bagaimana pendidikan Kristen mewujudkan misi profetik Gereja dengan mengintegrasikan nilai-nilai keadilan dalam kurikulumnya. Hasil temuan menunjukkan sinergi antara teologi sosial dan pendidikan Kristen, sekaligus mengidentifikasi tantangan seperti resistensi budaya, kekakuan teologis, dan inersia kelembagaan. Studi ini menyimpulkan bahwa model pendidikan yang berfokus pada keadilan perlu dikembangkan untuk memperlengkapi umat dalam mewujudkan suara profetik Gereja di tengah masyarakat.